Lipids from Lipomyces starkeyi - Robert Wild; Satish Patil; Milan Popović; Mark Zappi; Stephen Dufreche; Rakesh Bajpai (Food Technology and Biotechnology, 2010)
The oleaginous yeast Lipomyces starkeyi is interesting for industrial-scale production of biodiesel. Here it is reported that this yeast is able to digest unsaccharified, soluble potato starch. In these experiments, the cultivation time of Lipomyces starkeyi was reduced to half of the previously reported values. The effect of C:N molar ratio was studied on growth and lipid content of L. starkeyi in media containing glucose or potato starch as C-source. At a C:N molar ratio of 61.2 in glucose medium, the lipid content was measured at 30 % of the dry matter. It was established that the cellular lipid content increased with increasing C:N molar ratio, but the cell yield decreased. In a pH-controlled 1-litre agitated and aerated bioreactor, batch cultivation on glucose resulted in 23 % lipids in cells on dry mass basis (dm), cell yield of 0.25 g/g glucose, and lipid yield of 0.06 g/g glucose. Under the same operating conditions, fed-batch cultivation with discrete glucose additions resulted in 27 % lipids, cell yield of 0.28 g/g glucose, and lipid yield of 0.08 g/g glucose. On soluble but unsaccharified sweet potato starch, cell yield was 0.41 g/g glucose equivalent, lipid yield 0.16 g/g glucose equivalent, and lipid content in cells 40 %. The major fatty acids in the cells were C16:0 and C18:1 (accounting for 85–90 % by mass of the total lipids) with the rest being C16:1 and C18:0. All of these are valuable lipids for biodiesel production. Based on these results, wastes and wastewater from food industry and sewage sludge could serve as sources for the production of biodiesel.